Importance of over‐reading ambulatory ECG‐based microvolt T‐wave alternans to eliminate three main sources of measurement error. Issue 5 (26th June 2019) - Takasugi, Nobuhiro; Matsuno, Hiroko; Takasugi, Mieko; Shinoda, Koichi; Watanabe, Takatomo; Ito, Hiroyasu; Okura, Hiroyuki; Verrier, Richard L.
Abstract: Background: Ambulatory electrocardiogram (ECG)‐based microvolt T‐wave alternans values measured by the modified moving average method (MMA‐TWA) can be disrupted by T‐wave changes that mimic true repolarization alternans. Methods: We investigated potential sources of measurement error by studying 19 healthy subjects (12 men; median age, 25) free of known heart disease with 36‐month follow‐up to establish freedom from significant arrhythmia or syncope. All participants underwent 24‐hr continuous 12‐lead ECG monitoring. Causes of automated MMA‐TWA ≥42 µV episodes were classified based on visual inspection. Results: A total of 2, 189 episodes of automated MMA‐TWA episodes ≥42 µV were observed in all subjects (peak MMA‐TWA: median, 94 μV; interquartile range, 81–112 μV). All episodes included one or more beats with T‐wave deformation which lacked "repeating ABAB pattern" and therefore were identified as TWA measurement error. Causes of such error were categorized as: (a) artifact [72.6% (1, 589/2, 189), observed in 19 (100%) subjects], more frequently in limb than precordial leads; (b) T‐wave changes due to changes in heart/body position [25.5% (559/2, 189), observed in 14 (73.7%) subjects], frequently observed in leads V1‐2; and (c) postextrasystolic T‐wave changes [1.9% (41/2, 189), observed in 2 (10.5%) subjects]. Conclusions: Relying only on automated MMA‐TWA values obtained during ambulatory ECG monitoring can lead to incorrect measurement of TWA. Our findings offer the potential to reduce false‐positive TWA results and to achieve more accurate detection of true repolarization alternans.